2006
DOI: 10.1016/j.jfoodeng.2005.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Use of response surface methodology for optimization of xylitol production by the new yeast strain Debaryomyces hansenii UFV-170

Abstract: Aim of this work was the optimization of xylitol production by Debaryomyces hansenii UFV-170, which already proved to be a new promising xylitol-producing yeast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…They selected glucose, yeast extract, and (NH 4 ) 2 SO 4 as independent variables There are a few publications reporting the application of RSM in the production of xylitol, a polyol chemically and functionally similar to arabitol, from D-xylose, a pentose sugar component of the hemicellulosic fraction of plant biomass, which is similar to L-arabinose. Sampaio et al [15] ran a 3 3 full factorial design using the initial concentration of xylose, rotation speed and the starting biomass concentration of D. hansenii as independent variables, and determined maximum xylitol concentration, yield, productivity, and specific productivity as response variables. They showed that an increase in xylose concentration in the range of 55-165 g/l and a rotation speed in the range of 100-200 rpm resulted in a rise in xylitol concentration [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They selected glucose, yeast extract, and (NH 4 ) 2 SO 4 as independent variables There are a few publications reporting the application of RSM in the production of xylitol, a polyol chemically and functionally similar to arabitol, from D-xylose, a pentose sugar component of the hemicellulosic fraction of plant biomass, which is similar to L-arabinose. Sampaio et al [15] ran a 3 3 full factorial design using the initial concentration of xylose, rotation speed and the starting biomass concentration of D. hansenii as independent variables, and determined maximum xylitol concentration, yield, productivity, and specific productivity as response variables. They showed that an increase in xylose concentration in the range of 55-165 g/l and a rotation speed in the range of 100-200 rpm resulted in a rise in xylitol concentration [15].…”
Section: Discussionmentioning
confidence: 99%
“…Sampaio et al [15] ran a 3 3 full factorial design using the initial concentration of xylose, rotation speed and the starting biomass concentration of D. hansenii as independent variables, and determined maximum xylitol concentration, yield, productivity, and specific productivity as response variables. They showed that an increase in xylose concentration in the range of 55-165 g/l and a rotation speed in the range of 100-200 rpm resulted in a rise in xylitol concentration [15]. In another study, Vasquez et al [2] used RSM to optimize xylitol production from D-xylose by C. guilliermondii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors have been attributed for the low yields which include low or inappropriate application of inputs like clean seeds, fertilizers and control of the major potato diseases [5]. RSM emerged in the 1950s [6] within the context of Chemical Engineering in an attempt to construct empirical models able to find useful statistical relationships between all the variables making up an industrial system. Response surface methodology (RSM) has been a useful statistical technique for modeling and analyzing situations in which the response of interest is influenced by several variables and the objective is to optimize this response [7].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers observed that initial xylose concentration, co-factor regeneration and oxygen transfer were key factors for xylitol production [7]. Debaryomyces hansenii was observed to produce xylitol with product yields from 0.76 g/g to 0.78 g/g at 30°C and 200 rpm using Erlenmeyer flasks [8][9][10]. In a study using corn cob hemicellulose hydrolyzate, xylitol yields from xylose up to 0.73 g/g were observed using Candida tropicalis W103 at 35 °C [11].…”
Section: Introductionmentioning
confidence: 99%